Method for preparing stickers that can be peeled off easily and without residue

By treating the surface of the base paper and introducing polymer-coated carboxylated nanocellulose adhesive, the problem of glue residues in the peeling process of existing stickers is solved, and the effect of light peeling and no residue is achieved.

CN119775916APending Publication Date: 2025-04-08DONGGUAN DANGNA PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411959507.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing light peel stickers tend to leave glue residues during the peeling process, and the sticking reduction method depends on UV, electricity or heating, which has the problem of equipment dependence and inappropriateness of thermally sensitive substrates.

Method used

By treating the surface of the base paper and introducing a polymer-coated carboxylated nanocellulose adhesive, the swelling effect of the sticker is achieved by utilizing the swelling effect of the anion and cationic bonds and water.

Benefits of technology

The sticker is achieved without glue residue when peeled off and reduces dependence on the equipment, and is suitable for different types of substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775916A_ABST
    Figure CN119775916A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a sticker that can be easily peeled off and has no residue, which specifically comprises the following steps: step 1, preparing a polymer resin; step 2, preparing carboxyl nanocellulose; step 3, preparing a polymer-coated carboxyl nanocellulose adhesive according to step 1 and step 2; step 4, preparing a surface treatment agent; and step 5, preparing a sticker. The present invention solves the problem of adhesive peeling residue through the surface treatment of base paper and the strong anionic and cationic action of the adhesive; at the same time, the introduction of carboxymethyl cellulose in the surface treatment layer enhances the water permeability, and the adhesive layer contains anionic and cationic bonds, which react with water to swell and achieve easy peeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and relates to a method for preparing a sticker that can be easily peeled off and has no residue. Background Art

[0002] With the development of economy and society, stickers are widely used in various commodity anti-counterfeiting, advertising trademarks, fashion products, etc. However, most stickers are temporary and disposable, and need to be peeled off after use. At the same time, the adhered object is required to return to its original state during peeling. The characteristics of light peeling stickers are that the sticker and the adhered object need to have strong bonding strength. After use, they are treated by certain means, such as electrical, thermal, and optical treatment, to reduce the bonding strength between the sticker and the adhered object and achieve light peeling. During peeling, if you want no glue residue on the adhered object, it requires strong interaction between the molecules in the adhesive, and strong interaction between the adhesive and the substrate.

[0003] Up to now, the intermolecular forces in adhesives are usually strengthened by covalent bonds in crosslinkers or curing agents to solve the problem of adhesive residue. The light peeling function mainly uses UV, power, heating and other methods to reduce viscosity. These modes have certain defects. For example, UV and electrical viscosity reduction require light source and power supply, and heating is not conducive to use on heat-sensitive substrates. The development of new viscosity-reducing and residue-free stickers has a certain complementary significance. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an easy-to-peel, residue-free sticker, which solves the problem of adhesive peeling residue through surface treatment of base paper and strong anionic and cationic effects of the adhesive; at the same time, carboxymethyl cellulose is introduced into the surface treatment layer to enhance water permeability, and the adhesive layer contains anionic and cationic bonds, which react with water to swell and achieve easy peeling.

[0005] The technical solution adopted by the present invention is a method for preparing a sticker that can be peeled off easily and has no residue, which specifically comprises the following steps:

[0006] Step 1, preparing a polymer resin;

[0007] Step 2, preparing carboxyl nanocellulose;

[0008] Step 3, preparing a polymer-coated carboxyl nanocellulose adhesive according to step 1 and step 2;

[0009] Step 4, preparing a surface treatment agent;

[0010] Step 5: Prepare stickers.

[0011] The present invention is also characterized in that:

[0012] The specific process of step 1 is:

[0013] Take 10-20g of isooctyl acrylate, 0.5-1g of butyl acrylate, 0.5-1g of isobornyl acrylate, 0.05-0.1g of triacrylate glycerol and 5-10g of acryloyloxyethyl trimethylammonium chloride and add them to 20-40mL of N,N-dimethylformamide solution, then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene, stir for 10-20min, continue to add 20-30mg of azobisisobutyronitrile, raise the temperature to 65-80℃ and react for 1-2h, cool to room temperature after the reaction, pour the reaction solution into 100-200mL of industrial alcohol to obtain a white precipitate product, wash it three times with 100-200mL of industrial alcohol to obtain a polymer resin.

[0014] The specific process of step 2 is:

[0015] Step 2.1, homogenize bamboo pulp with a beating degree of 80°-90° in a high-pressure homogenizer for 30-50 times, then add it to 200-400 mL of water for ultrasonic dispersion for 20-30 minutes, and then add 0.014-0.028 g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6-12 g of sodium hydroxide in sequence;

[0016] Step 2.2, adding 1-2 mol / L NaOH aqueous solution to the reaction solution obtained in step 2.1, adjusting the pH value of the solution to 10-11; then adding 4.2-8.2 g of sodium hypochlorite and stirring continuously for 2-3 hours; adjusting the pH value to 7 by adding hydrochloric acid to obtain a suspension, filtering the suspension and washing with 500-800 mL of deionized water, repeating 5-8 times to obtain gel-like carboxyl nanocellulose, and finally configuring the carboxyl nanocellulose into a carboxy nanocellulose suspension with a solid content of 0.03-0.06 wt%.

[0017] The specific process of step 3 is:

[0018] Step 3.1, dissolve 1-2 g of polymer resin in 20-30 mL of N,N-dimethylformamide solution to obtain a polymer solution, and let stand for 12-24 hours;

[0019] Step 3.2, dropwise adding the polymer solution obtained in step 3.1 into a carboxyl nanocellulose suspension having a solid content of 0.03-0.06 wt%, the dropping time being 60-90 min, stirring while dropping, and the stirring rate being 1000-1200 r / min; dialyzing the obtained reaction solution in a 7000-10000 Da dialysis bag and 500-1000 mL deionized water for 12-18 h, repeating 3-5 times, and then freeze-drying at -70°C for 72 h to obtain polymer-coated carboxyl nanocellulose;

[0020] Step 3.3, add 15-30 mL of xylene to the polymer-coated carboxyl nanocellulose, and mix in an internal mixer for 10-15 minutes to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0021] The specific process of step 4 is:

[0022] Take 5-10g of isooctyl acrylate, 0.5-1g of butyl acrylate, 2-4g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05-0.1g of triacrylate and 0.2-0.4g of ethyl isocyanate acrylate and add them to 20-30mL of N,N-dimethylformamide solution; then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene, stir the solution for 10-20min, continue to add 20-30mg of azobisisobutyronitrile, and raise the temperature to 65-80 ℃ for 1-2h, then add 1-2g of carboxymethyl cellulose and continue stirring for 3-6h, pour the reaction solution into 100-200mL of industrial alcohol to obtain a white precipitate product, wash the white precipitate three times with 100-200mL of industrial alcohol to obtain a solid product, then add 5-10mL of castor oil and 2-4mL of acrylic acid to the solid product and mix in an internal mixer for 10-20min, continue to add 5-10mg of azobisisobutyronitrile and 0.05-0.1g of triacrylate glycerol, stir evenly to obtain a surface treatment agent.

[0023] The specific process of step 5 is:

[0024] Step 5.1, take a base paper with a length of 20 cm and a width of 10 cm, apply a layer of surface treatment agent with a thickness of 5-10 um on the upper surface of the base paper, and then continuously irradiate under a 45W ultraviolet lamp for 15-20 seconds to obtain a surface treatment layer; Step 5.2, apply a layer of polymer-coated carboxyl nanocellulose adhesive with a thickness of 15-20 um on the surface treatment layer to obtain a polymer-coated carboxyl nanocellulose adhesive layer;

[0025] Step 5.3, applying a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker.

[0026] The beneficial effects of the present invention are as follows: the present invention adopts polymer resin and carboxyl nanocellulose to construct a polymer-coated carboxyl nanocellulose adhesive, utilizes the anionic and cationic bonds and hydrophilic swelling properties formed therebetween, and constructs a surface treatment layer between the adhesive layer and the base paper, thereby strengthening the force between the adhesive and the base paper and solving the problem of peeling residue. At the same time, the introduction of carboxymethyl cellulose in the surface treatment layer is conducive to water entering the adhesive layer, and utilizes the hydrophilic and swelling effects of the anionic and cationic adhesive to achieve the functions of no adhesive residue and easy peeling when the sticker is peeled off. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The sticker structure is prepared in the method for preparing a sticker that can be easily peeled off and has no residue;

[0028] Figure 2 This is a comparison chart of the water contact angles of the adhesive layers of stickers prepared in Example 1 of the method for preparing an easy-to-peel, residue-free sticker of the present invention and Comparative Examples 2 to 4. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] The method for preparing a sticker that can be easily peeled off and has no residues comprises the following steps:

[0031] Step 1, preparation of polymer resin, specifically:

[0032] Take 10-20g of 2-ethylhexanoate, 0.5-1g of butyl acrylate, 0.5-1g of acrylate isobornyl, 0.05-0.1g of glycerol triacrylate and 5-10g of acryloyloxyethyl trimethylammonium chloride and add them to 20-40mL of N,N-dimethylformamide solution. Then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10-20min. Continue to add 20-30mg of azobisisobutyronitrile, raise the temperature to 65-80℃ and react for 1-2h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100-200mL of industrial alcohol to obtain a white precipitate product, which is washed three times with 100-200mL of industrial alcohol to obtain a polymer resin.

[0033] Step 2, preparation of carboxyl nanocellulose, specifically:

[0034] Bamboo pulp (2-4g, dry weight) with a beating degree of 80°-90° is homogenized 30-50 times in a high-pressure homogenizer, then added to 200-400mL of water for ultrasonic dispersion for 20-30 minutes, and then 0.014-0.028g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6-12g of sodium hydroxide are gradually added. Then, 1-2mol / L of NaOH aqueous solution is added to the above reaction solution, and its pH value is adjusted to 10-11. Then 4.2-8.2g of sodium hypochlorite is gradually added and stirred continuously for 2-3 hours. The pH value is adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 500-800mL of deionized water, repeat 5-8 times to obtain gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose is configured into a suspension with a solid content of 0.03-0.06wt%.

[0035] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0036] Take 1-2g of polymer resin and dissolve it in 20-30mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 12-24h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.03-0.06wt%. The dropping time is 60-90min, and the stirring is rapid while dropping, and the stirring speed is 1000-1200r / min. The obtained reaction solution is dialyzed for 12-18h in a 7000-10000Da dialysis bag and 500-1000mL deionized water, and repeated 3-5 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 15-30mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 10-15min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0037] Step 4, preparing a surface treatment agent, specifically:

[0038] Take 5-10g of 2-ethylhexanoate, 0.5-1g of butyl acrylate, 2-4g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05-0.1g of glycerol triacrylate and 0.2-0.4g of ethyl isocyanate acrylate and add them to 20-30mL of N,N-dimethylformamide solution. Then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10-20min. Continue to add 20-30 mg of azobisisobutyronitrile, raise the temperature to 65-80°C and react for 1-2 hours, then add 1-2 g of carboxymethyl cellulose and continue stirring for 3-6 hours, pour the reaction solution into 100-200 mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 100-200 mL of industrial alcohol to obtain a solid product, then add 5-10 mL of castor oil and 2-4 mL of acrylic acid to the solid product and mix in an internal mixer for 10-20 minutes, continue to add 5-10 mg of azobisisobutyronitrile and 0.05-0.1 g of triacrylate glycerol, stir evenly, and obtain a surface treatment agent.

[0039] Step 5, preparation and application of stickers, specifically:

[0040] like Figure 1 As shown, the sticker structure is a four-layer structure, including from bottom to top: base paper layer, surface treatment layer, adhesive layer, and release layer. Specifically, take a base paper with a length of 20cm and a width of 10cm, apply a layer of surface treatment agent with a thickness of 5-10um on the surface of the base paper, and then irradiate it under a 45W ultraviolet lamp for 15-20s. Then apply a layer of polymer-coated carboxyl nanocellulose adhesive 15-20um on the surface treatment layer. Finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 10-15N for 5-10s. When peeling the sticker from the glass surface, first apply warm water of 50-60℃ on the surface of the sticker for 10-15s, and then peel it off.

[0041] Example 1

[0042] Step 1, preparation of polymer resin, specifically:

[0043] Take 10g of 2-ethylhexanoate acrylate, 0.5g of butyl acrylate, 0.5g of isobornyl acrylate, 0.05g of triacrylate glycerol and 5g of acryloyloxyethyl trimethylammonium chloride and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile and raise the temperature to 65℃ for 1h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 100mL of industrial alcohol to obtain a polymer resin.

[0044] Step 2, preparation of carboxyl nanocellulose, specifically:

[0045] Bamboo pulp (2g, dry weight) with a beating degree of 80° was homogenized 30 times in a high-pressure homogenizer, then added to 200mL of water for ultrasonic dispersion for 20 minutes, and then 0.014g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6g of sodium hydroxide were gradually added at a given molar ratio. Then, a 1mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 10. Then 4.2g of sodium hypochlorite was gradually added and stirred continuously for 2 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 500mL of deionized water, repeat 5 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.03wt%.

[0046] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0047] Take 1g of polymer resin and dissolve it in 20mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 12h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.03wt%. The dropping time is 60min, and the stirring is rapid while dropping, and the stirring speed is 1000r / min. The obtained reaction solution is dialyzed for 12h with a 7000Da dialysis bag and 500mL of deionized water, and repeated 3 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 15mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 10min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0048] Step 4, preparing a surface treatment agent, specifically:

[0049] Take 5g of isooctyl acrylate, 0.5g of butyl acrylate, 2g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05g of triacrylate and 0.2g of isocyanate ethyl acrylate and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile, raise the temperature to 65℃ and react for 1h, then add 1g of carboxymethyl cellulose and continue stirring for 3h, pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 100mL of industrial alcohol to obtain a solid product, then add 5mL of castor oil and 2mL of acrylic acid to the solid product and knead in a mixer for 10min, continue to add 5mg of azobisisobutyronitrile and 0.05g of triacrylate, stir evenly to obtain a surface treatment agent.

[0050] Step 5, preparation and application of stickers, specifically:

[0051] Take a 20cm long and 10cm wide base paper, apply a layer of surface treatment agent on the surface of the base paper with a thickness of 5um, and then irradiate it under a 45W ultraviolet lamp for 15s. Then apply a layer of polymer-coated carboxyl nanocellulose adhesive 15um on the surface treatment layer; finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 10N for 5s. When peeling the sticker from the glass surface, first apply 50℃ warm water on the sticker surface for 10s, and then peel it off.

[0052] Comparative Example 1 (When preparing the polymer resin, the cationic monomer acryloyloxyethyl trimethyl ammonium chloride was not added, the polymer resin became hydrophobic, and could not form anionic and cationic binding forces with the carboxyl nanocellulose, and the polymer coating of the carboxyl nanocellulose adhesive failed)

[0053] Step 1, preparation of polymer resin, specifically:

[0054] Take 10g of 2-ethylhexanoate, 0.5g of butyl acrylate, 0.5g of acrylate, and 0.05g of glycerol triacrylate and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile and raise the temperature to 65℃ for 1h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 100mL of industrial alcohol to obtain a polymer resin.

[0055] Step 2, preparation of carboxyl nanocellulose, specifically:

[0056] Bamboo pulp (2g, dry weight) with a beating degree of 80° was homogenized 30 times in a high-pressure homogenizer, then added to 200mL of water for ultrasonic dispersion for 20 minutes, and then 0.014g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6g of sodium hydroxide were gradually added at a given molar ratio. Then, a 1mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 10. Then 4.2g of sodium hypochlorite was gradually added and stirred continuously for 2 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 500mL of deionized water, repeat 5 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.03wt%.

[0057] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0058] Take 1g of polymer resin and dissolve it in 20mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 12h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.03wt%. The dropping time is 60min, and the stirring is rapid while dropping, and the stirring speed is 1000r / min. The obtained reaction solution is dialyzed for 12h with a 7000Da dialysis bag and 500mL of deionized water, and repeated 3 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 15mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 10min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0059] Comparative Example 2 (the polymer resin was not coated with carboxyl nanocellulose, and the adhesive was directly prepared, and there was residue after peeling, and the peeling force was high)

[0060] Step 1, preparation of polymer resin, specifically:

[0061] Take 10g of 2-ethylhexanoate acrylate, 0.5g of butyl acrylate, 0.5g of isobornyl acrylate, 0.05g of triacrylate glycerol and 5g of acryloyloxyethyl trimethylammonium chloride and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile and raise the temperature to 65℃ for 1h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 100mL of industrial alcohol to obtain a polymer resin. Add 15mL of xylene to the polymer resin and mix it in a mixer for 10min to obtain a polymer adhesive.

[0062] Step 2, surface treatment agent, specifically:

[0063] Take 5g of isooctyl acrylate, 0.5g of butyl acrylate, 2g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05g of triacrylate and 2g of isocyanate ethyl acrylate and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile, raise the temperature to 65℃ and react for 1h, then add 1g of carboxymethyl cellulose and continue stirring for 3h, pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 100mL of industrial alcohol to obtain a solid product, then add 5mL of castor oil and 2mL of acrylic acid to the solid product and mix in a mixer for 10min, continue to add 5mg of azobisisobutyronitrile and 0.05g of triacrylate, stir evenly to obtain a surface treatment agent.

[0064] Step 3, preparation and application of stickers, specifically:

[0065] Take a 20cm long and 10cm wide base paper, apply a layer of surface treatment agent with a thickness of 5um on the surface of the base paper, and then irradiate it under a 45W ultraviolet lamp for 15s. Then apply a layer of polymer adhesive 15um on the surface treatment layer. Finally, apply a layer of release paper on the surface of the polymer adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 10N for 5s. When peeling the sticker from the glass surface, first apply 50℃ warm water on the sticker surface for 10s, and then peel it off.

[0066] Comparative Example 3 (When preparing the sticker, the surface was not treated, and the polymer-coated carboxyl nanocellulose adhesive was directly coated on the base paper, and there was residue after peeling)

[0067] Step 1, preparation of polymer resin, specifically:

[0068] Take 10g of 2-ethylhexanoate acrylate, 0.5g of butyl acrylate, 0.5g of isobornyl acrylate, 0.05g of triacrylate glycerol and 5g of acryloyloxyethyl trimethylammonium chloride and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile and raise the temperature to 65℃ for 1h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 100mL of industrial alcohol to obtain a polymer resin.

[0069] Step 2, preparation of carboxyl nanocellulose, specifically:

[0070] Bamboo pulp (2g, dry weight) with a beating degree of 80° was homogenized 30 times in a high-pressure homogenizer, then added to 200mL of water for ultrasonic dispersion for 20 minutes, and then 0.014g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6g of sodium hydroxide were gradually added at a given molar ratio. Then, a 1mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 10. Then 4.2g of sodium hypochlorite was gradually added and stirred continuously for 2 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 500mL of deionized water, repeat 5 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.03wt%.

[0071] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0072] Take 1g of polymer resin and dissolve it in 20mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 12h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.03wt%. The dropping time is 60min, and the stirring is rapid while dropping, and the stirring speed is 1000r / min. The obtained reaction solution is dialyzed for 12h with a 7000Da dialysis bag and 500mL of deionized water, and repeated 3 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 15mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 10min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0073] Step 4, preparation and application of stickers, specifically:

[0074] Take a 20cm long and 10cm wide base paper, and apply a 15um layer of polymer-coated carboxyl nanocellulose adhesive on the base paper. Finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 10N for 5s. When peeling the sticker from the glass surface, first apply 50℃ warm water on the sticker surface for 10s, and then peel it off.

[0075] Comparative Example 4 (the surface treatment agent does not contain carboxymethyl cellulose, the surface treatment layer is hydrophobic, water cannot pass through the surface treatment layer into the adhesive layer, and the peeling force is high)

[0076] Step 1, preparation of polymer resin, specifically:

[0077] Take 10g of 2-ethylhexanoate acrylate, 0.5g of butyl acrylate, 0.5g of isobornyl acrylate, 0.05g of triacrylate glycerol and 5g of acryloyloxyethyl trimethylammonium chloride and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile and raise the temperature to 65℃ for 1h. After the reaction is completed, cool to room temperature and pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 100mL of industrial alcohol to obtain a polymer resin.

[0078] Step 2, preparation of carboxyl nanocellulose, specifically:

[0079] Bamboo pulp (2g, dry weight) with a beating degree of 80° was homogenized 30 times in a high-pressure homogenizer, then added to 200mL of water for ultrasonic dispersion for 20 minutes, and then 0.014g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6g of sodium hydroxide were gradually added at a given molar ratio. Then, a 1mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 10. Then 4.2g of sodium hypochlorite was gradually added and stirred continuously for 2 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 500mL of deionized water, repeat 5 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.03wt%.

[0080] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0081] Take 1g of polymer resin and dissolve it in 20mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 12h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.03wt%. The dropping time is 60min, and the stirring is rapid while dropping, and the stirring speed is 1000r / min. The obtained reaction solution is dialyzed for 12h with a 7000Da dialysis bag and 500mL of deionized water, and repeated 3 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 15mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 10min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0082] Step 4, surface treatment agent, specifically:

[0083] Take 5g of isooctyl acrylate, 0.5g of butyl acrylate, 2g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05g of triacrylate and 0.2g of isocyanate ethyl acrylate and add them to 20mL of N,N-dimethylformamide solution. Then add 0.3mg of 1-methyl-2,2-diphenylethylene and stir the solution for 10min. Continue to add 20mg of azobisisobutyronitrile, raise the temperature to 65℃ and react for 1h, pour the reaction solution into 100mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 100mL of industrial alcohol to obtain a solid product, then add 5mL of castor oil and 2mL of acrylic acid to the solid product and mix in a mixer for 10min, continue to add 5mg of azobisisobutyronitrile and 0.05g of triacrylate, stir evenly to obtain a surface treatment agent.

[0084] Step 5, preparation and application of stickers, specifically:

[0085] Take a 20cm long and 10cm wide base paper, apply a layer of surface treatment agent with a thickness of 5um on the surface of the base paper, and then irradiate it under a 45W ultraviolet lamp for 15s. Then apply a layer of polymer-coated carboxyl nanocellulose adhesive 15um on the surface treatment layer. Finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 10N for 5s. When peeling the sticker from the glass surface, first apply 50℃ warm water on the sticker surface for 10s, and then peel it off.

[0086] The stickers prepared in Example 1 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1:

[0087] Table 1 Analysis results of Example 1 and Comparative Examples 1-4

[0088]

[0089] It can be seen from Table 1 that the sticker in Example 1 has a relatively high viscosity on the peeling surface, and the peeling force reaches 275 mN·(25 mm). -1 After warm water treatment, the peeling force is reduced to 85mN·(25mm) -1 This is mainly because the anionic carboxyl nanocellulose and cationic polymer resin in the adhesive layer form anionic and cationic bonds, which have a strong effect on water, causing the polymer-coated carboxyl nanocellulose adhesive to swell and reduce viscosity.

[0090] In Comparative Example 1, cationic monomer acryloyloxyethyltrimethylammonium chloride was not added during the preparation of the polymer resin, and the polymer resin became hydrophobic and could not form anionic and cationic binding forces with the carboxyl nanocellulose. The polymer resin could not be dissolved in water. Therefore, when mixed with the carboxyl nanocellulose, the polymer resin components separated and the polymer-coated carboxyl nanocellulose adhesive failed.

[0091] In comparative example 2, the polymer resin was not coated with carboxyl nanocellulose, and the polymer adhesive was directly prepared. Therefore, there were no nanoparticles in the polymer adhesive, and the adhesive was directly in contact with the peeling, and its contact area was large, resulting in a large peeling force. In addition, after the sticker was treated with water, the peeling force was reduced to 160mN·(25mm) -1 Since the polymer adhesive does not form a strong anionic and cationic bond with the carboxyl nanocellulose, there is some residue left after the adhesive is peeled off.

[0092] In Comparative Example 3, when preparing the sticker, the polymer-coated carboxyl nanocellulose adhesive was directly coated on the base paper without surface treatment. Since the base paper and the polymer-coated carboxyl nanocellulose were not firmly bonded, there were residues when peeling.

[0093] In Comparative Example 4, carboxymethyl cellulose was not added to the surface treatment agent, the surface treatment layer was hydrophobic, water could not pass through the surface treatment layer into the adhesive layer, and the peeling force was high. No adhesive residue was left during peeling.

[0094] After the sticker was treated with warm water, the peeling force changed, mainly because water entered the adhesive. Therefore, the water contact angle of the sticker adhesive layer was tested to indicate the hydrophilicity and hydrophobicity. Figure 2 As shown. Since the chemical structures of the adhesive layers in Example 1 and Comparative Examples 3-4 are the same, their water contact angles are similar. The water contact angle of Comparative Example 2 is relatively low, mainly because the adhesive layer does not have nano-protrusions formed by nanomaterials. However, after being treated with warm water, the peeling force of Comparative Example 2 is higher, mainly because without the nano-protrusions, the contact area between the adhesive layer and the glass is large, so the peeling force increases.

[0095] While the water contact angles of the adhesive layers of Example 1 and Comparative Examples 3-4 are similar, the peeling force and adhesive residue after warm water treatment are quite different. The viscosity of the surface treated layer is related to the hydrophilicity and hydrophobicity.

[0096] Example 2

[0097] Step 1, preparation of polymer resin, specifically:

[0098] Take 15g of 2-ethylhexanoate acrylate, 0.8g of butyl acrylate, 0.8g of isobornyl acrylate, 0.08g of triacrylate glycerol and 8g of acryloyloxyethyl trimethylammonium chloride and add them to 30mL of N,N-dimethylformamide solution. Then add 0.4mg of 1-methyl-2,2-diphenylethylene and stir the solution for 15min. Continue to add 25mg of azobisisobutyronitrile and raise the temperature to 75℃ to react for 1.5h. After the reaction is completed, cool to room temperature and pour the reaction solution into 150mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 150mL of industrial alcohol to obtain a polymer resin.

[0099] Step 2, preparation of carboxyl nanocellulose, specifically:

[0100] Bamboo pulp (3g, dry weight) with a beating degree of 85° was homogenized 40 times in a high-pressure homogenizer, then added to 300mL of water for ultrasonic dispersion for 25 minutes, and then 0.024g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 8g of sodium hydroxide were gradually added at a given molar ratio. Then, a 1.5mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 10. Then 6.2g of sodium hypochlorite was gradually added and stirred continuously for 2.5 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 700mL of deionized water, repeat 6 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.04wt%.

[0101] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0102] Take 1.5g of polymer resin and dissolve it in 25mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 18h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.04wt%. The dropping time is 80min, and the stirring is rapid while dropping, and the stirring speed is 1100r / min. The obtained reaction solution is dialyzed for 16h with an 8000Da dialysis bag and 800mL of deionized water, and repeated 4 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 25mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 12min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0103] Step 4, preparing a surface treatment agent, specifically:

[0104] Take 8g of 2-ethylhexanoate, 0.8g of butyl acrylate, 3g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.08g of triacrylate and 0.3g of ethyl isocyanate acrylate and add them to 25mL of N,N-dimethylformamide solution. Then add 0.4mg of 1-methyl-2,2-diphenylethylene and stir the solution for 15min. Continue to add 25mg of azobisisobutyronitrile, raise the temperature to 75℃ and react for 1.5h, then add 1.5g of carboxymethyl cellulose and continue stirring for 4h, pour the reaction solution into 150mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 150mL of industrial alcohol to obtain a solid product, then add 8mL of castor oil and 3mL of acrylic acid to the solid product and knead in a mixer for 15min, continue to add 8mg of azobisisobutyronitrile and 0.08g of triacrylate, stir evenly to obtain a surface treatment agent.

[0105] Step 5, preparation and application of stickers, specifically:

[0106] Take a 20cm long and 10cm wide base paper, apply a layer of surface treatment agent on the surface of the base paper with a thickness of 8um, and then irradiate it under a 45W ultraviolet lamp for 18s. Then apply a layer of polymer-coated carboxyl nanocellulose adhesive 15um on the surface treatment layer; finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 12N for 8s. When peeling the sticker from the glass surface, first apply 55℃ warm water on the sticker surface for 12s, and then peel it off.

[0107] Example 3

[0108] Step 1, preparation of polymer resin, specifically:

[0109] Take 20g of 2-ethylhexanoate acrylate, 1g of butyl acrylate, 1g of isobornyl acrylate, 0.1g of triacrylate glycerol and 10g of acryloyloxyethyl trimethylammonium chloride and add them to 40mL of N,N-dimethylformamide solution. Then add 0.6mg of 1-methyl-2,2-diphenylethylene and stir the solution for 20min. Continue to add 30mg of azobisisobutyronitrile and raise the temperature to 80℃ for 2h. After the reaction is completed, cool to room temperature and pour the reaction solution into 200mL of industrial alcohol to obtain a white precipitate product. Wash it three times with 200mL of industrial alcohol to obtain a polymer resin.

[0110] Step 2, preparation of carboxyl nanocellulose, specifically:

[0111] Bamboo pulp (4g, dry weight) with a beating degree of 90° was homogenized 50 times in a high-pressure homogenizer, then added to 400mL of water for ultrasonic dispersion for 30 minutes, and then 0.028g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 12g of sodium hydroxide were gradually added at a given molar ratio. Then, a 2mol / L aqueous NaOH solution was added to the above reaction solution to adjust its pH value to 11. Then 8.2g of sodium hypochlorite was gradually added and stirred continuously for 3 hours. The pH value was adjusted to 7 by adding hydrochloric acid to obtain a suspension. Filter and wash with 800mL of deionized water, repeat 8 times to obtain a gel-like carboxyl nanocellulose, and finally the carboxyl nanocellulose was configured into a suspension with a solid content of 0.06wt%.

[0112] Step 3, polymer-coated carboxyl nanocellulose adhesive, specifically:

[0113] Take 2g of polymer resin and dissolve it in 30mL of N,N-dimethylformamide solution to obtain a polymer solution, and further let the polymer solution stand for 24h. Then add the polymer solution drop by drop into the carboxyl nanocellulose suspension with a solid content of 0.06wt%. The dropping time is 90min, and the stirring is rapid while dropping, and the stirring speed is 1200r / min. The obtained reaction solution is dialyzed for 18h in a 10000Da dialysis bag and 1000mL of deionized water, and repeated 5 times. Then freeze-dry at minus 70℃ for 72h. Get polymer-coated carboxyl nanocellulose. Add 30mL of xylene to the polymer-coated carboxyl nanocellulose, and mix it in a mixer for 15min to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

[0114] Step 4, preparing a surface treatment agent, specifically:

[0115] Take 10g of isooctyl acrylate, 1g of butyl acrylate, 4g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.1g of triacrylate and 0.4g of isocyanate acrylate ethyl and add them to 30mL of N,N-dimethylformamide solution. Then add 0.6mg of 1-methyl-2,2-diphenylethylene and stir the solution for 20min. Continue to add 30mg of azobisisobutyronitrile, raise the temperature to 80℃ and react for 2h, then add 2g of carboxymethyl cellulose and continue stirring for 6h, pour the reaction solution into 200mL of industrial alcohol to obtain a white precipitate product, wash the precipitate three times with 200mL of industrial alcohol to obtain a solid product, then add 10mL of castor oil and 4mL of acrylic acid to the solid product and mix in a mixer for 20min, continue to add 10mg of azobisisobutyronitrile and 0.1g of triacrylate, stir evenly to obtain a surface treatment agent.

[0116] Step 5, preparation and application of stickers, specifically:

[0117] Take a 20cm long and 10cm wide base paper, apply a layer of surface treatment agent with a thickness of 10um on the base paper, and then irradiate it under a 45W ultraviolet lamp for 20s. Then apply a layer of polymer-coated carboxyl nanocellulose adhesive 20um on the surface treatment layer; finally, apply a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker. When testing the performance of the sticker, peel off the surface release paper, then stick the sticker on the glass surface and press it with a force of 15N for 10s. When peeling the sticker from the glass surface, first apply 60℃ warm water on the sticker surface for 15s, and then peel it off.

Claims

1. A method for preparing a sticker that can be peeled off easily and has no residue, characterized in that: The specific steps include: Step 1, preparing a polymer resin; Step 2, preparing carboxyl nanocellulose; Step 3, preparing a polymer-coated carboxyl nanocellulose adhesive according to step 1 and step 2; Step 4, preparing a surface treatment agent; Step 5: Prepare stickers.

2. The method for preparing a sticker that is easy to peel off and has no residue according to claim 1, characterized in that: The specific process of step 1 is as follows: Take 10-20g of isooctyl acrylate, 0.5-1g of butyl acrylate, 0.5-1g of isobornyl acrylate, 0.05-0.1g of triacrylate glycerol and 5-10g of acryloyloxyethyl trimethylammonium chloride and add them to 20-40mL of N,N-dimethylformamide solution, then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene, stir for 10-20min, continue to add 20-30mg of azobisisobutyronitrile, raise the temperature to 65-80℃ and react for 1-2h, cool to room temperature after the reaction, pour the reaction solution into 100-200mL of industrial alcohol to obtain a white precipitate product, wash it three times with 100-200mL of industrial alcohol to obtain a polymer resin.

3. The method for preparing a sticker that is easy to peel off and has no residue according to claim 2, characterized in that: The specific process of step 2 is: Step 2.1, homogenize bamboo pulp with a beating degree of 80°-90° in a high-pressure homogenizer for 30-50 times, then add it to 200-400 mL of water for ultrasonic dispersion for 20-30 minutes, and then add 0.014-0.028 g of 2,2,6,6-tetramethylpiperidinyl nitrogen and 6-12 g of sodium hydroxide in sequence; Step 2.2, adding 1-2 mol / L NaOH aqueous solution to the reaction solution obtained in step 2.1, adjusting the pH value of the solution to 10-11; then adding 4.2-8.2 g of sodium hypochlorite and stirring continuously for 2-3 hours; adjusting the pH value to 7 by adding hydrochloric acid to obtain a suspension, filtering the suspension and washing with 500-800 mL of deionized water, repeating 5-8 times to obtain gel-like carboxyl nanocellulose, and finally configuring the carboxyl nanocellulose into a carboxy nanocellulose suspension with a solid content of 0.03-0.06 wt%.

4. The method for preparing a sticker that can be peeled off easily and has no residue according to claim 3, characterized in that: The specific process of step 3 is as follows: Step 3.1, dissolve 1-2 g of polymer resin in 20-30 mL of N,N-dimethylformamide solution to obtain a polymer solution, and let stand for 12-24 hours; Step 3.2, dropwise adding the polymer solution obtained in step 3.1 into a carboxyl nanocellulose suspension having a solid content of 0.03-0.06 wt%, the dropping time being 60-90 min, stirring while dropping, and the stirring rate being 1000-1200 r / min; dialyzing the obtained reaction solution in a 7000-10000 Da dialysis bag and 500-1000 mL deionized water for 12-18 h, repeating 3-5 times, and then freeze-drying at -70°C for 72 h to obtain polymer-coated carboxyl nanocellulose; Step 3.3, add 15-30 mL of xylene to the polymer-coated carboxyl nanocellulose, and mix in an internal mixer for 10-15 minutes to obtain a gel-like polymer-coated carboxyl nanocellulose adhesive.

5. The method for preparing a sticker that can be peeled off easily and has no residue according to claim 3, characterized in that: The specific process of step 4 is as follows: Take 5-10g of isooctyl acrylate, 0.5-1g of butyl acrylate, 2-4g of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 0.05-0.1g of triacrylate and 0.2-0.4g of ethyl isocyanate acrylate and add them to 20-30mL of N,N-dimethylformamide solution; then add 0.3-0.6mg of 1-methyl-2,2-diphenylethylene, stir the solution for 10-20min, continue to add 20-30mg of azobisisobutyronitrile, and raise the temperature to 65-80 ℃ for 1-2h, then add 1-2g of carboxymethyl cellulose and continue stirring for 3-6h, pour the reaction solution into 100-200mL of industrial alcohol to obtain a white precipitate product, wash the white precipitate three times with 100-200mL of industrial alcohol to obtain a solid product, then add 5-10mL of castor oil and 2-4mL of acrylic acid to the solid product and mix in an internal mixer for 10-20min, continue to add 5-10mg of azobisisobutyronitrile and 0.05-0.1g of triacrylate glycerol, stir evenly to obtain a surface treatment agent.

6. The method for preparing a sticker that can be peeled off easily and has no residue according to claim 5, characterized in that: The specific process of step 5 is as follows: Step 5.1, take a base paper with a length of 20 cm and a width of 10 cm, apply a layer of surface treatment agent with a thickness of 5-10 um on the upper surface of the base paper, and then continuously irradiate under a 45W ultraviolet lamp for 15-20 seconds to obtain a surface treatment layer; Step 5.2, apply a layer of polymer-coated carboxyl nanocellulose adhesive with a thickness of 15-20 um on the surface treatment layer to obtain a polymer-coated carboxyl nanocellulose adhesive layer; Step 5.3, applying a layer of release paper on the surface of the polymer-coated carboxyl nanocellulose adhesive layer to obtain a sticker.